STUDENTS’ PERCEPTION IN USING QUIZIZZ AS ONLINE LEARNING MEDIA IN SECOND LANGUAGE CLASSROOM - Fathira, Vina; Masbiran, Gunaldi; Elsara, Wenny; Asril, Lelly Zuyana (JURNAL ILMU PENDIDIKAN, 2024)
Information and communication technology, or ICT, has expanded quickly and has an influence on the entire world. Teachers may use technology to improve English language learning opportunities in a variety of situations. Using Quizizz, a media application with educational advantages, may facilitate online learning by encouraging students to learn innovatively and actively response to questions, which makes it simpler to carry out in class. The purpose of this study is to find out the students’ perception in using Quizizz as online learning media in second language classroom. This is a quantitative study conducted utilising questionnaires. This questionnaire was filled out by 20 students. The statements are questions would be like in the following: 1. Quizizz is interesting and fun in online class (English Linguistic class), 2. Quizizz has an attractive display in English Linguistic class, 3. Quizizz has many challenging features in English Linguistic class, 4. I enjoy doing the test using Quizizz, 5. Quizizz feels like a game, 6. Quizizz doesn’t make me tense in doing the test, 7. I can’t cheat during the test using Quizizz, 8. Quizizz creates a competitive atmosphere, 9. I feel encouraged to be number one on the leaderboard, and 10. Quizizz is better than the traditional test. The data for this study was collected by asking students to fill out a Google form with a statement and four Likert scale options, which were then analysed by calculating the percentage and number of student selections. The study's findings demonstrate the benefits of using Quizizz as an online learning tool, including: 1) student interest; 2) Tense for positive meaning; and 3) competition. In other words, while there are numerous advantages to utilising Quizizz as an online learning medium, there is one disadvantage: the subject is not fully absorbed.